Crystallization and preliminary X-ray diffraction studies of hexokinase KlHxk1 from Kluyveromyces lactis - Kuettner, E. Bartholomeus (International Union of Crystallography, 2007)

(untitled)
Glucose acts as both a carbon source and a hormone-like regulator of gene expression in eukaryotic organisms from yeast to man. Phosphorylation of glucose is executed by hexokinases, which represent a class of multifunctional enzymes that, in addition to their contribution to the uptake and initiation of metabolism of glucose, fructose and mannose, are involved in glucose signalling. The genome of the budding yeast Kluyveromyces lactis encodes a single hexokinase (KlHxk1) and a single glucokinase (KlGlk1). KlHxk1 exists in a monomer–homodimer equilibrium which is presumed to play a role in metabolic regulation. In order to evaluate the physiological significance of KlHxk1 dimerization on a molecular level, the enzyme was crystallized and subjected to X-ray structure analysis. Crystallization employing ammonium sulfate, diammonium phosphate or polyethylene glycol 6000 at pH values of 8.0–9.5 gave seven different crystal forms of KlHxk1. Crystallographic data to 1.66 Å resolution were obtained using synchrotron radiation. Structure determination of KlHxk1 in various packing environments will reveal the full architecture of the homodimeric enzyme and complete our mechanistic understanding of the catalytic and regulatory functions of the enzyme.